The Mediating Role of Pedagogical Competence in the Relationship between Competency-Based Training and Early Childhood Learning Outcomes - Novidiyanti, Farida; Sutarto, Joko; Avrilianda, Decky (Jurnal Penelitian Pendidikan, 2025)
This study examines the direct and indirect effects of competency-based training (CBT) on early childhood learning outcomes, mediated by the pedagogical competence of early childhood education (PAUD) teachers in Semarang Regency. Using a quantitative explanatory research design with a cross-sectional survey, data were collected from 153 PAUD teachers and their students through validated questionnaires and documentation. Findings indicate that CBT positively and significantly influences both early childhood learning outcomes and teachers' pedagogical competence. Furthermore, pedagogical competence also significantly influences children's learning outcomes. Most importantly, this study demonstrates that pedagogical competence acts as a significant mediator in the relationship between CBT and early childhood learning outcomes. These results underscore the importance of structured and ongoing professional development for PAUD teachers to enhance their pedagogical skills, which in turn is crucial for improving the quality of early childhood education.